Sintering kinetics of nanometric calcium oxide in vacuum atmosphere. Issue 6 (July 2015) - Ramos, J.P.; Fernandes, C.M.; Stora, T.; Senos, A.M.R.
Abstract: A recent application for nanometric CaO powder is its use as a spallation target material for the production of isotope beams at CERN. The stability of the nanostructure at high operation temperatures is a crucial feature to provide stable and improved isotope release rates. Prior to operation, sintering studies under thermal conditions similar to those of the target operation are required to establish the microstructural evolution due to coarsening and densification processes. This knowledge enables the identification of the limiting temperatures for the target operation, ensuring a stable nanostructure for higher and constant isotope release rates. In this study, nanometric CaO powder with 58 m 2  g −1 of specific surface area was obtained from vacuum decomposition of calcium carbonate at 800 °C. The microstructure evolution of porous powder compacts was investigated under vacuum atmosphere, from 1000 to 1250 °C, for holding times from 3 to 600 min. For temperatures higher than 1000 °C, a significant surface area reduction was observed, accompanied by porosity decrease. The morphological analysis of the pore evolution revealed a differential sintering of the porous compacts, mainly occurring inside the aggregates. The kinetic analysis of the surface area reduction pointed to aggregate shrinkage controlled by volume diffusion with surface diffusion as an underlying mechanism for lower temperatures.